The role and impact of Del(5q) and TP53 mutations on haematopoietic stem and progenitor cells during the progression of Myelodysplastic Syndrome to Acute Myeloid Leukaemia - Doolittle, H (2017)
Myelodysplastic Syndromes (MDS) are a heterogeneous group of haematological malignancies characterised by ineffective haematopoiesis and dysplastic bone marrow changes. Patients frequently progress to Acute Myeloid Leukaemia and this is associated with very poor clinical outcomes. This thesis focusses on a subtype of MDS, Del(5q) MDS. Sequencing analysis revealed that Del(5q) is frequently the initiating lesion in low risk isolated Del(5q) MDS and tracking patients over time demonstrated progressive disease is associated with the acquisition of new mutations (including Tp53 mutations). Early in disease, MDS appears to be sustained by the Lin-CD34+CD38-CD90+CD45RA- MDS stem cells. In one patient, however, at the point of disease progression and after the acquisition of a Tp53 mutation, self-renewal activity could be detected in a progenitor cell population outside the stem cell compartment. On the basis of these findings and previous evidence linking Tp53 mutations with progression of Del(5q) MDS, mouse models were used to investigate if and how Del(5q) and mutant Tp53 collaborate to perturb haematopoiesis. An established model of Del(5q) (heterozygous deletion of Cd74-Nid67) was combined with a Tp53 knockout model and conditional knockin models of Tp53 mutations found in MDS patients. This work showed Tp53 loss and mutations collaborate with Del(5q) to alter haematopoietic stem/ progenitor cell number, function and differentiation ability. Del(5q)+/-Tp53-/- cells also uniquely develop long-term self-renewal potential in vitro which can be associated with chromosomal instability. Preliminary evidence also suggests a possible role for Del(5q) itself in the development of chromosomal instability.